Pediatric kidney transplantation, a technical update. Issue 4 (August 2021) - Etesami, Kambiz; Hogen, Rachel; Lestz, Rachel
Abstract : Purpose of review: Pediatric kidney transplantation is the definitive therapy for infants and children suffering from renal failure. It is a distinct endeavor demanding specialized care for optimal results. This includes a dedicated preoperative workup accounting for unique predisposing urologic conditions, specialized surgical techniques, and careful hemodynamic monitoring and maintenance. Recent findings: Historically, size-matched renal allografts from pediatric donors to pediatric recipients suffered from poor outcomes. Advances in surgical technique performed at high volume centers have shown that these operations can be performed safely, helping expand the donor pool for these patients. Concurrently, transplantation of increasingly small for size infants with complex medical and surgical backgrounds has become a reality. Summary: On a policy front, efforts to expand access to size-matched organs, combined with advances in medical management and immunosuppression have seen pediatric renal transplantation reach new heights. Now, these breakthroughs are heightened by the ability to transplant such organs into the smallest infants. The net result will be diminished transplant waiting times and, accordingly, improved quality of life and longevity for children suffering from renal failure.